2021
DOI: 10.3390/cancers13133206
|View full text |Cite
|
Sign up to set email alerts
|

Current Systemic Treatment Options in Metastatic Urothelial Carcinoma after Progression on Checkpoint Inhibition Therapy—A Systemic Review Combined with Single-Group Meta-Analysis of Three Studies Testing Enfortumab Vedotin

Abstract: Background: In the first and second-line therapy of metastatic urothelial carcinoma (mUC), checkpoint inhibitors (CPI) such as Pembrolizumab and Atezolizumab have been widely implemented. Little is currently known about what therapeutic options are effective after therapy with CPI. This article presents a systemic review of current treatment options in this setting. Methods: From August 2020 to 15 April 2021, a literature search was performed through the PubMed/Medline. Subsequently, a single-group meta-analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 80 publications
0
9
0
Order By: Relevance
“…Limited data are available on the effectiveness of these treatment options in such patients. A recent publication in muBC patients who showed disease progression following immune checkpoint inhibition, supports the use of the antibody-drug-conjugate enfortumab vedotin (72). Several studies of novel combinations of immune checkpoint inhibitors with other agents are ongoing; thus, we anticipate a continuous and rapid evolution of the treatment landscape of metastatic bladder and kidney cancer.…”
Section: Radiotherapy Combined With Novel Anticancer Agentsmentioning
confidence: 93%
“…Limited data are available on the effectiveness of these treatment options in such patients. A recent publication in muBC patients who showed disease progression following immune checkpoint inhibition, supports the use of the antibody-drug-conjugate enfortumab vedotin (72). Several studies of novel combinations of immune checkpoint inhibitors with other agents are ongoing; thus, we anticipate a continuous and rapid evolution of the treatment landscape of metastatic bladder and kidney cancer.…”
Section: Radiotherapy Combined With Novel Anticancer Agentsmentioning
confidence: 93%
“…To this day, there is still significant uncertainty regarding the best treatment course in platinum-refractory mUC patients pretreated with ICI. While the most reliable data are available for the antibody–drug conjugate enfortumab vedotin [ 15 ], there is a lack of knowledge in regard to other treatment options, highlighted in a recently published systemic review by Deiniger et al [ 12 ]. In Europe, also after the recent EMA-approval for enfortumab vedotin, vinflunine is still a standard of care after failure of sequential platinum-based chemotherapy and ICI treatment [ 2 , 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…A real-world data analysis by Bamias et al showed superior efficacy with an overall response rate (ORR) of 18% and a tolerable safety profile of vinflunine in an unselected mUC population of 797 patients [ 10 ]. To date, little evidence exists about the use of vinflunine as a third-line agent after pretreatment with platinum-based chemotherapy and checkpoint inhibition [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…NLR was calculated by dividing the absolute neutrophil count by the absolute lymphocyte count in the peripheral blood. The cutoff values for Hb, Alb, CRP, and NLR were derived from the area under the receiver operating characteristic (ROC) curve [22] and defined as the minimal values for (1 − sensitivity) 2 + (1 − specificity) 2 . In addition, the patients were divided into two groups according to the BOR: those who achieved CR or PR (responder group) or SD or PD (non-responder group).…”
Section: Patient Evaluationmentioning
confidence: 99%
“…Metastatic urothelial carcinoma (mUC) is an aggressive urological cancer, and the prognosis of patients with mUC remains poor, with a 5-year overall survival (OS) of only 4.6% [ 1 , 2 ]. Although platinum-based combination chemotherapy has been the first-line systemic treatment for mUC over the last two decades, the median OS has been reported to be 12–15 months [ 1 , 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%